Design and Construction of Electrical System for Bread Dough Proofer Tool Based on a Microcontroller with PID Control on Donut Dough - Hidayati, Alfiana Nur; Mahartana, Ida Bagus Putu Putra; Serfandi, Dina Novera; Fahmiy, Muh Ilham; Prayogo, Dhanang Suryo (LPPM Universitas Dian Nuswantoro, 2025)
This study focuses on the design and implementation of an electrical system for a bread dough proofer tool, specifically optimized for donut dough fermentation, utilizing a microcontroller with Proportional-Integral-Derivative (PID) control. The proofing process is crucial for dough quality, and maintaining precise temperature and humidity conditions is essential for consistent results. The PID control algorithm continuously calculates the error between desired setpoints and measured process variables, adjusting actuator outputs to minimize this error. The PID parameters were tuned using a trial-and-error method to achieve optimal response speed and stability, with values of , , and . Experimental results demonstrate the system’s effectiveness in stabilizing the proofing environment. The temperature was maintained at 40.10 with a minimal overshoot of 0.30 and a rise time of 10.25 minutes. Humidity was regulated within the range of 80-90% RH for 38.4 minutes, with a rise time of 40.41 minutes. The system exhibited robust disturbance rejection, quickly recovering from external perturbations. Compared to manual proofing, the automated system reduced proofing time by approximately 25% and significantly improved donut dough quality, evidenced by enhanced volume expansion and uniform texture. Keywords - Bread Dough Proofer, PID Control, Microcontroller, Temperature and Humidity Control, Automated Proofing System